The effect of lesser yam based cookies on fasting glucagon-like peptide 1, appetite, and dietary intake in overweight/obese with ad libitum diet - Harry Freitag Luglio Muhammad; Annisa Lailatul Fitria; Dewi Ayu Kusumawardhani; Rinta Amalia; Desy Dwi Hapsari; Rina Susilowati; Sunarti Sunarti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2019)
Background: Appetite and dietary intake have been associated with obesity and successfulness of weight loss in obese individuals. Glucagon-like peptide 1 is a gut-derived neuropeptide that is produced as a response to dietary intake and associated with appetite. It has been investigated that prebiotic can induce GLP-1 production in animal models and humans. Objectives: This study aimed to investigate the effect of lesser yam based cookies on fasting GLP-1 plasma, appetite, and dietary intake. Methods: An experimental study was conducted on 15 overweight/obese individuals using cookies made with lesser yam flour for 6 weeks. Fasting GLP-1 level, dietary intake, and appetite were measured before and after the intervention. Dietary intake was recorded using a semi-quantitative food frequency questionnaire and appetite was measured using a visual analog scale. Results: After the intervention, the dietary intake includes total energy (p=0,013), protein (p=0,004) and carbohydrate (p=0,02) were significantly reduced. Based on paired t-test that was done in each time point, after the intervention subjects had lower hunger feeling and higher satiety especially at 4 (p=0,039) and 3 (p=0,039) hours after breakfast, respectively. Fasting GLP-1 plasma level was not changed after the intervention (p>0,05). There is no correlation between GLP-1 and dietary intake as well as appetite. Conclusions: We concluded that lesser yam based cookies were able to reduce dietary intake and hunger as well as increase fullness. The fasting GLP-1 concentration did not change after the intervention this was not associated with changes in satiety, fullness, desire to eat, or energy intake.